A Conditioned Medium of Umbilical Cord Mesenchymal Stem Cells Overexpressing Wnt7a Promotes Wound Repair and Regeneration of Hair Follicles in Mice - Liang Dong; Haojie Hao; Jiejie Liu; Dongdong Ti; Chuan Tong; Qian Hou; Meirong Li; Jingxi Zheng; Gang Liu; Xiaobing Fu; Weidong Han (Stem Cells International)
Mesenchymal stem cells (MSCs) can affect the microenvironment of a wound and thereby accelerate wound healing. Wnt proteins act as key mediators of skin development and participate in the formation of skin appendages such as hair. The mechanisms of action of MSCs and Wnt proteins on skin wounds are largely unknown. Here, we prepared a Wnt7a-containing conditioned medium (Wnt-CM) from the supernatant of cultured human umbilical cord-MSCs (UC-MSCs) overexpressing Wnt7a in order to examine the effects of this CM on cutaneous healing. Our results revealed that Wnt-CM can accelerate wound closure and induce regeneration of hair follicles. Meanwhile, Wnt-CM enhanced expression of extracellular matrix (ECM) components and cell migration of fibroblasts but inhibited the migratory ability and expression of K6 and K16 in keratinocytes by enhancing expression of c-Myc. However, we found that the CM of fibroblasts treated with Wnt-CM (HFWnt-CM-CM) can also promote wound repair and keratinocyte migration; but there was no increase in the number of hair follicles of regeneration. These data indicate that Wnt7a and UC-MSCs have synergistic effects: they can accelerate wound repair and induce hair regeneration via cellular communication in the wound microenvironment. Thus, this study opens up new avenues of research on the mechanisms underlying wound repair.